The Adaptation from Online Learning to Face to-Face Learning during the post of Covid-19 Pandemic: The Case of One Senior High School in Batam - Yanti, Novia Sri; Khaidir, Afriva (Universitas Jambi, Indonesia, 2023)
This research aimed to identify the process of adaptation from online learning to face-to-face learning in post-Covid-19 and describe the extent to which students and teachers can adapt from online learning to face-to-face in post-Covid-19. This research used the theory of habitus and environment by Pierre Bourdieu. It used qualitative with case study research. The research participants were the teachers, students, and curriculum assistant principals of SMAN 15 Batam. Data validity tests include credibility, transferability, dependability, and confirmability tests. Meanwhile, data analysis used the interactive analysis model Miles and Huberman (2002). The research results showed that the process of adapting online learning to face-to-face has stages of preparation, implementation, and learning. The level of achievement of teachers and students in adapting to learning can be seen from the learning methods used by teachers, attendance, and student tardiness.